Bovine Meat and Milk Factor (BMMF) protein is expressed in macrophages spread widely over the mucosa of colorectal cancer patients - Siqin, Sumen; Nikitina, Ekaterina; Rahbari, Mohammad; Ernst, Claudia; Krunic, Damir; Birgin, Emrullah; Teßmer, Claudia; Hofmann, Ilse; Rahbari, Nuh Nabi; Bund, Timo (Cells, 2025)
Red meat consumption is considered a risk factor for colorectal cancer (CRC) development and stimulated isolation of plasmid-like DNA molecules from bovine serum and milk, termed bovine meat and milk factors (BMMFs). BMMFs encode a conserved replication protein (Rep). Increased populations of Rep-expressing macrophages have been identified in the peritumor of CRC patients and pre-cancerous tissues when compared to the tissues of healthy individuals. This supports the concept that BMMFs increase cancer risk by indirect carcinogenesis, upon induction of chronic inflammation. However, the spread of Rep+ immune cells in tissues at greater distances from primary tumors has not yet been assessed. Here, we immunohistologically analyzed the presence of Rep+ immune cells in sets of tumor, peritumor and, additionally, distant tissues of CRC patients (n = 13). We identified consistently high numbers of BMMF-positive macrophages in mucosal tissues at distances of as much as 25 cm away from the primary tumors, at levels comparable to peritumors and associated with M2-like macrophage polarization. The broad distribution of BMMFs suggests that BMMF+ macrophages might already exist at stages of pre-cancerous dysplasia or before. Quantification of BMMF tissue expression during colonoscopy might help to preventively stratify individuals at risk of developing polyps/CRC and recommend them for enhanced surveillance and/or changes in dietary lifestyle.